Suicide mortality among individuals in federal prisons compared with the general population: a retrospective cohort study in the USA from 2009 to 2020 - Lauren Brinkley-Rubinstein; Katherine LeMasters; Shabbar Ranapurwala; Mike Dolan Fliss; Michael Forrest Behne; Emilie Duchesneau; Jennifer Lao (BMJ Public Health)
Introduction Suicide is one of the leading causes of death in US prisons. Yet, administrative data lags years behind and reporting rarely accounts for differing age distributions between suicide rates between incarcerated and general populations. Our objective was to compare reported suicides rate among those incarcerated in federal prisons and the general population, accounting for age distributions, before and during the COVID-19 pandemic (2009–2020).Methods Using data from the Federal Bureau of Prison, Bureau of Justice Statistics and the Centers for Disease Control and Prevention WONDER database and a retrospective cohort study design, we estimated age-standardised mortality rates and standardised mortality ratios comparing observed suicide mortality among those incarcerated in federal prisons to the expected mortality if they experienced the same age-specific suicide rates as the general population. We tested for linear trends over calendar year in each population.Results In federal prisons, 245 deaths were reported as suicides from 2009 to 2020 (5% of federal prison deaths). From 2009 to 2020, the observed suicide rate in prisons increased from 10.57 to 19.01 per 100 000 and the crude suicide rate in the general population increased from 15.41 to 17.26 per 100 000. After age standardisation, the observed suicide rate in prisons was lower than the suicide rate in the general population between 2009 and 2019, but surpassed it in 2020. In 2020, we observed 1.07 (95% CI: 0.74 to 1.57) times the number of suicides than we would expect if the prison population had the same age-stratified risk of suicide as the general population.Conclusions Increasing suicide mortality in prisons is a public health crisis. In 2020, the age-standardised suicide rate in prison surpassed that of the general population, despite the incarcerated population being under high surveillance. To improve public health, decarceration community-based mental healthcare are promising solutions. Additionally, there is an urgent need for improved cause of death reporting quality in prisons.